Coronavirus Disease 2019 Vaccination During Pregnancy and Breastfeeding: A Review of Evidence and Current Recommendations in Europe, North America, and Australasia - Pietrasanta, Carlo; Ronchi, Andrea; Crippa, Beatrice Letizia; Artieri, Giacomo; Ballerini, Claudia; Crimi, Riccardo; Mosca, Fabio; Pugni, Lorenza (Frontiers in Pediatrics, 2022)
In late 2020, less than one year into the COVID-19 pandemic, several anti-SARS-CoV-2 vaccines were introduced on a worldwide scale, with a significant positive impact on the consequences of the disease for several high-risk population groups. In case of most bacterial or viral respiratory infections pregnant women are at increased risk of complications, but neither pregnant nor breastfeeding women were included in the first round of randomized clinical trials evaluating the safety and effectiveness of COVID-19 vaccines, because of safety and ethical concerns. Nevertheless, most anti-SARS-CoV-2 vaccines have not been expressly contraindicated during pregnancy or breastfeeding, and observational data on immune response, adverse effects, and clinical efficacy in pregnant and breastfeeding women have been progressively gathered during 2021. The vast majority of these data is reassuring for what concerns side effects for women and infants, and point out the efficacy of vaccines in protecting women against COVID-19-related complications. Despite this, hesitancy of pregnant and breastfeeding women at being vaccinated is still real. In this mini review, we resume the available data on the clinical consequences of COVID-19 in pregnant women, as well as adverse effects, systemic and mucosal immune response, and clinical effectiveness of COVID-19 vaccines in pregnant and breastfeeding women. Moreover, we offer an updated overview of European, North American, and Australasian recommendations concerning COVID-19 vaccination in pregnant and breastfeeding women, in order to safely ensure the highest protection of women and their infants.